Social robotics for children: an investigation of manufacturers’ claims - Dosso, Jill A.; Riminchan, Anna; Robillard, Julie M. (Frontiers in Robotics and AI, 2023)
As the market for commercial children’s social robots grows, manufacturers’ claims around the functionality and outcomes of their products have the potential to impact consumer purchasing decisions. In this work, we qualitatively and quantitatively assess the content and scientific support for claims about social robots for children made on manufacturers’ websites. A sample of 21 robot websites was obtained using location- independent keyword searches on Google, Yahoo, and Bing from April to July 2021. All claims made on manufacturers’ websites about robot functionality and outcomes (n = 653 statements) were subjected to content analysis, and the quality of evidence for these claims was evaluated using a validated quality evaluation tool. Social robot manufacturers made clear claims about the impact of their products in the areas of interaction, education, emotion, and adaptivity. Claims tended to focus on the child rather than the parent or other users. Robots were primarily described in the context of interactive, educational, and emotional uses, rather than being for health, safety, or security. The quality of the information used to support these claims was highly variable and at times potentially misleading. Many websites used language implying that robots had interior thoughts and experiences; for example, that they would love the child. This study provides insight into the content and quality of parent-facing manufacturer claims regarding commercial social robots for children.